The impact of reforestation with broad-leaved and coniferous species on soil properties and carbon storage (Case study: Kolet Forest) - Khadijeh Asghari; Hamid Jalilvand; Hamed Asadi (علوم محیطی)
Introduction: Soil is the largest source of carbon in the biosphere and more than half of its carbon is stored in forest ecosystems. Considering the importance of the soil carbon, the purpose of this research is to investigate how different species of broadleaf and coniferous species affect forest carbon storage in soil, considering their different ability to store and use soil nutrients in the forest Kolet.Material and Methods: In this research, first, three stands of Acer velutinum Boiss, Alnus subcordata C.A.M, and Cupressus sempervirens var horizontalis, as well as one natural forest stand were selected in the study area. Ten samples of 400 square meters (20Î20 meters) were selected in each cluster. Also, soil samples were collected from the four corners and the center of each plot from a depth of 0-15 cm; Then the soils were mixed and a combined sample was separated for the laboratory analyses (40 samples in total), which was used to study the physical and chemical characteristics of the soil (bulk density, soil texture, soil reaction, electrical conductivity, organic carbon, total nitrogen, phosphorus and absorbable potassium). SAS statistical software was used for soil data analysis related variables, and the Vegan R software package was used for principal component analysis (PCA) to identify the most significant factor and differentiate between the studied populations.Results and Discussion: Based on the obtained results, soil reaction rate, absorbable potassium, relative humidity, organic carbon, clay and soil carbon storage had significant differences among the four stands (P < 0.01). Alnus subcordata and Acer velutinum showed the highest amount of carbon storage compared to Cupressus sempervirens and natural forest stand. The difference observed in the amount of soil organic carbon in the studied stands depended on the different capabilities of tree species in restoring the soil ecosystem. The planting of broadleaf species resulted in more carbon storage in the short term than coniferous species, because broadleaf tree species increase litter production and nutrient return, making them more effective in restoring degraded forest soils. This is due to faster leaf decomposition, higher nitrogen content and lower C/N ratio, while the presence of resinous and phenolic substances in coniferous leaves negatively affects the decomposition of their litter.Conclusion: In summary, this research showed that reforestation with broadleaf species in various areas of the region significantly impacted the soil carbon stock and carbon storage potential based on the type of tree species. Particularly, broadleaf species such as Alnus subcordata and Acer velutinum played a crucial role in increasing the amount of carbon stored in the soil of the studied region.